Refractory splenic tuberculosis in acute myeloid Leukemia: The role of advanced diagnostics and surgical intervention - Hongju Yan; Qin Wen; Xi Zhang (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
AML patients are at a high risk of opportunistic infections, with tuberculosis (TB) being a common and challenging one. The immunosuppression caused by both AML and its treatment heightens this risk. Diagnosing TB in AML patients is difficult due to the overlapping symptoms of AML and TB. This case report presents a 22-year-old man diagnosed with AML who developed disseminated TB, manifesting as a refractory tuberculous splenic abscess. Despite achieving complete remission from initial induction chemotherapy, the patient experienced persistent fever. Next-generation sequencing revealed Mycobacterium tuberculosis infection, and anti-TB treatment was initiated. Despite regular anti-tuberculosis therapy, the patient continued to have recurrent fevers, with progressive splenic enlargement and an increase in splenic lesions. Eventually, splenectomy confirmed the presence of abscess-type splenic tuberculosis and resolved the symptoms. Despite the recurrence of leukemia in the bone marrow and the development of central nervous system leukemia during the patient’s treatment, complete remission was achieved again after re - induction chemotherapy and intrathecal chemotherapy. Then the patient underwent successful HSCT. This case highlights the diagnostic and therapeutic challenges in managing disseminated TB in AML patients. It underscores the importance of early and accurate diagnosis using advanced molecular techniques, close monitoring, and aggressive treatment. Surgical interventions should also be considered when standard treatments fail. Additionally, it emphasizes the need for proactive TB screening and prevention strategies in high-risk populations, such as AML patients undergoing chemotherapy.